Positive Screens for Psychiatric Disorders in Primary Care: A Long-Term Follow-Up of Patients Who Were Not in Treatment - Weissman, Myrna M. (2010)
OBJECTIVE: Screening for psychiatric disorders has gained acceptance in some general medical settings, but critics argue about its value. The purpose of this study was to determine the clinical utility of screening by conducting a long-term follow-up of patients who screened positive for psychiatric disorders but who were initially not in treatment. METHODS: A cohort of 519 low-income, adult primary care patients were screened for major depression and bipolar, anxiety, and substance use disorders and reassessed with the Structured Clinical Interview for DSM-IV after a mean of 3.7 years by a clinician blind to the initial screen. Data on treatment utilization was obtained through hospital records. The sample consisted of 348 patients who had not received psychiatric care in the year before screening. RESULTS: Among 39 patients who screened positive for major depression, 62% (95% confidence interval=45.5%–77.6%) met criteria for current major depressive disorder at follow-up. Those who screened positive reported significantly poorer mental and social functioning and worse general health at follow-up than the screen-negative patients and were more likely to have visited the emergency department for psychiatric reasons (12.1% and 3.0%, odds ratio [OR]=6.4) and to have major depression (OR=7.6). Generally similar results were observed for patients who screened positive for other disorders. CONCLUSIONS: Commonly used screening methods identified patients with psychiatric disorders; about four years later, those not initially in treatment were likely to have enduring symptoms and to use emergency psychiatric services. Screening should be followed up by clinical diagnostic assessment in the context of available mental health treatment.